Disaster Preparedness and the Chronic Disease Needs of Vulnerable Older Adults - Nancy Aldrich; William F. Benson (Centers for Disease Control and Prevention, 2008)
About 80% of older adults have at least one chronic condition that makes them more vulnerable than healthy people during a disaster. These chronic conditions - combined with the physiological, sensory, and cognitive changes experienced as part of aging - result in frail older adults having special needs during emergencies. Planning and coordination among public health and emergency preparedness professionals and professionals who provide services for the aging are essential to meet these special needs. Several tools and strategies already exist to help prepare these professionals to protect and assist older adults during a disaster. These include having professionals from diverse fields work and train in coalitions, ensuring that advocates for older adults participate in community-wide emergency preparedness, and using community mapping data to identify areas where many older adults live.